Unraveling the evolution of southernmost Peru between 100 and 50 Ma through U-Pb geochronology of the Toquepala Group: Implications for exploration of large porphyry copper deposits - Sempere, Thierry (2021)
Integration of the zircon U-Pb ages available on the Toquepala Group, La Caldera batholith (s.l.), and porphyry Cu systems, in combination with geochemical data, unravels the evolution of the magmatic arc of southernmost Peru during the Late Cretaceous and Early Paleogene. Arc magmatic production increased starting ~90 Ma, and culminated between ~74 and ~62 Ma through a flare-up characterized by large plutonic and volcanic (especially ignimbritic) volumes. This long process resulted in the thickening of the arc crust, to a state of overthickening that triggered its extensional collapse, starting diachronously 61–59 Ma, during which giant porphyry Cu systems were emplaced between ~60 and ~53 Ma. Our empirical reconstruction of this protracted evolution provides simple guides for exploration of giant porphyry Cu deposits in southern Peru, as well as a magmatotectonic theoretical framework.